Selective visual attention and intelligence: evidence of validity for the escala de atenção seletiva visual - Fernandes Sisto, Fermino (2012)
The aim of this research was to look for two kinds of evidence of validity for the Escala de Atenção Seletiva Visual (EASE). Firstly, the means of two contrasted group was analyzed, and then the scale EASE was correlated with the Teste de Raciocínio Inferencial. This research involved 119 students (M=22,96 and DP=5,67), most of them female (79%). The scores of the Escala de Atenção Seletiva e Visual ranged from four to 30 points, while the Teste de Raciocínio Inferencial ranged from zero to 36. The differences of means were compared between the contrasted groups (t=-2,47; df=63; p=0,017), which indicated that one test could discriminate the other. Besides, a positive and significant coefficient of correlation (r=0,24; p=0,01) between total scores of the tests was detected. Therefore, the objective of this study was achieved, since two evidences of validity (a convergent-discriminant and by extreme groups) were found.